Experimental investigation on the shear capacity of RC beams with curtailed reinforcement. (15th August 2018) - Joergensen, Henrik B.; Hansen, Søren G.
Highlights: 28 new tests of reinforced concrete beams with variations of curtailed reinforcement. Shear capacity and crack development are studied. The tests show that the curtailed reinforcement does not influence the shear capacity. It is shown that codes overestimate the shear capacity in some specific cases. Abstract: In continuous beams with both positive and negative moments, curtailed reinforcement is often used to increase the bending capacity locally. In practice, it is normally considered as a safe assumption to neglect the curtailed reinforcement when calculating the shear capacity. However, some tests from the literature have indicated that the end of curtailed reinforcement may decrease the shear capacity. Not all shear models take this effect into account. These models tend to overestimate the shear capacity significantly. This paper presents a large experimental study on the effect from curtailed reinforcement on the shear capacity of continuous beams without shear reinforcement. The study shows that the curtailed reinforcement does not significantly influence the shear capacity. Beams with curtailed reinforcement have the same or only slightly reduced shear capacity compared to similar beams without curtailed reinforcement. Different shear models ability to predict the test result are investigated. (1) Eurocode 2, that does not take the effect of curtailed reinforcement into account, overestimates the shear capacity of the tested beams by approximately 20%. (2) fib Model Code 2010, which account for the effect of the curtailed reinforcement, predicts the shear capacity of the tested beams with curtailed reinforcement quite accurately. However, since the shear capacity of the tested beams was not significantly affected by the presence of curtailed reinforcement, the model overestimates the shear capacity of similar beams without curtailed reinforcement by approximately 20%. Based on the results presented in this paper, it is the authors' opinion that the reduced shear capacity should mainly be attributed to the continuous beam test setup rather than the curtailed reinforcement.